(untitled) (Castilla. Estudios de Literatura, 2013)
The article describes the relationships between literature and symbolic market in Poesía civil by the Argentinian poet Sergio Raimondi, in the context of globalization. We considre that they are organized around a melancholic regime that redefines them. The “regime” category reintroduces the studies by Roger Chartier in Escribir las prácticas, when he points out that that Foucauldian notion refers to the relationship between the discourse and their practices.